STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEDISIPLINAN SANTRI PROGRAM TAKHASUS PERSATUAN GURU AGAMA ISLAM PADANG - Ediwan; Martin Kustati; Gusmirawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the strategies used by Islamic Education (PAI) teachers in improving the discipline of students in the Takhasus Program of the Persatuan Guru Agama Islam (PGAI) Padang. The background of this research arises from the still weak level of discipline among several students, indicating the need for systematic, targeted, and continuous guidance. This study focuses on identifying the strategies applied by teachers, the supporting and inhibiting factors, and the effectiveness of these strategies in shaping students' disciplinary behavior. Using a qualitative approach with a descriptive method, data were collected through observation, in-depth interviews, and documentation. The stages of the research consisted of identifying discipline-related issues, mapping the teacher’s strategies, analyzing the implementation of these strategies, and drawing conclusions. The results show that PAI teachers apply several main strategies, including exemplary behavior, habituation through daily rules, spiritual motivation, and strengthening a conducive learning environment. Supporting factors include teacher commitment, institutional support, and the religious culture of the pesantren, while inhibiting factors involve differences in student character and limited supervision outside formal learning hours. Overall, these strategies proved effective in gradually improving students’ discipline within the Takhasus Program.